Microsoft Excel formulas & functions for dummies - Bluttman, Ken (--For dummies., 2016)
"Excel is a tool that's equally useful for analyzing your investments and cataloging you recipes. So why not claim all the power it offers? This book shows you how to take advantage of over 150 built-in Excel functions that you can use in formulas to crunch numbers for just about every purpose. Best of all, it explains everything in plain English! "--Page 4 of cover